A bismuth ferrite-barium titanate piezoelectric ceramic with a heterostructure and a preparation method thereof

CN119390439BActive Publication Date: 2026-10-23GUILIN UNIV OF ELECTRONIC TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411551338.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2026-10-23
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

BiFeO3-BaTiO3基陶瓷由于其高的居里温度TC≈454℃而备受关注,但是其低压电性能d33≤120pC/N而限制了其应用,一般通过传统的离子掺杂、引入第三元、工艺优化等方法去调控

Benefits of technology

[0022]1)本发明通过ABA叠层结构(BST-BFBT-BST),通过离子扩散技术在BiFeO3-BaTiO3陶瓷表面形成异质结构,提高该体系Bi(Ba)、Fe位离子混乱度和弛豫铁电特性,增强该体系的退极化温度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390439B_ABST
    Figure CN119390439B_ABST
Patent Text Reader

Abstract

The application provides a bismuth ferrite-barium titanate piezoelectric ceramic with a heterogeneous structure and a preparation method thereof. (1‑x) Sn x O3; and the B layer has a structure general formula: 0.75BiFeO3-0.25BaTiO3-y% MnO2; 0 The preparation method comprises the following steps: sequentially laminating and pressing A layer raw materials and B layer raw materials to obtain a blank sheet, and then arranging glue, electroplating and polarization to obtain the piezoelectric ceramic. The piezoelectric ceramic has piezoelectric performance and thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of piezoelectric ceramics technology, specifically to a bismuth ferrite-barium titanate piezoelectric ceramic with a heterostructure and its preparation method. Background Technology

[0002] Piezoelectric ceramics possess the ability to convert between electrical and mechanical energy, and are widely used in weaponry, aerospace, security alarms, medical equipment, home appliances, and oil exploration. Currently, Pb-based piezoelectric ceramics, represented by lead zirconate titanate (PZT), are renowned for their excellent piezoelectric properties (d...). 33 Lead-free piezoelectric ceramics (≥300 pC / N) and high Curie temperatures (Tc ≥ 300℃) dominate the commercial market. With increasing awareness of the health risks and environmental protection associated with lead, its use has been legally restricted. This has prompted the search for and development of lead-free piezoelectric ceramics as effective alternatives to PZT, making the search for novel high-temperature lead-free piezoelectric ceramics an urgent priority.

[0003] Currently popular lead-free piezoelectric ceramics include (Bi 0.5 Na 0.5 TiO3(T) C ≈320℃), BiFeO3-BaTiO3(T C ≈454℃), (K 0.5 Na 0.5 )NbO3(T C ≈420℃), BaTiO3(T C ≈115℃). BiFeO3-BaTiO3 based ceramics have a high Curie temperature Ti. C It has attracted much attention due to its temperature of approximately 454℃, but its low voltage electrical performance... 33 The piezoelectric constant d is limited by a value ≤120 pC / N, and its application is generally controlled by traditional methods such as ion doping, introduction of a tertiary element, and process optimization. The literature (S.Guan, H.Yang, G.Qiao, et al., Journal of Electronic Materials, 2020, 49(10): p.6199-6207) obtained the piezoelectric constant d by adding Li2CO3 and CuO to 0.7BF-0.3BT lead-free piezoelectric ceramics. 33 It boasts excellent piezoelectric properties of 168 pC / N, but sacrifices thermal stability while achieving enhanced piezoelectric performance, which is detrimental to the high-temperature application of BiFeO3-BaTiO3-based ceramics. Summary of the Invention

[0004] This invention provides a bismuth ferrite-barium titanate piezoelectric ceramic with good piezoelectric properties and thermal stability and a heterostructure, as well as its preparation method.

[0005] The technical solution provided by this invention is a bismuth ferrite-barium titanate piezoelectric ceramic with a heterostructure, which is formed by sequentially stacking and pressing an A layer material, a B layer material, and an A layer material.

[0006] The structural formula of the A-layer material is: BaTi (1-x) Sn x O3;

[0007] The general structural formula of the B-layer material is: 0.75BiFeO3-0.25BaTiO3-ywt%MnO2;

[0008] Where x represents the mole fraction, 0 < x ≤ 0.16; y = weight of MnO2 / total weight of B layer material × 100, and 0 < y ≤ 1.

[0009] Preferably, the weight ratio of layer A material, layer B material, and layer A material is 1:2.5:1.

[0010] As a preferred value, 0.07≤x≤0.16, 0.1≤y≤0.7.

[0011] More preferably, x = 0.07, y = 0.1.

[0012] This invention also provides a method for preparing bismuth ferrite-barium titanate piezoelectric ceramics with heterostructures, comprising the following steps:

[0013] 1) Using SnO2, BaCO3, and TiO2 as raw materials, according to BaTi (1-x) Sn x The O3 chemical formula is used to prepare the ingredients, and anhydrous ethanol is used as the solvent for grinding. After drying, the material is fired at 1150℃~1200℃ for 3~6 hours to obtain the A layer material.

[0014] 2) Using Bi2O3, Fe2O3, BaCO3, and TiO2 as raw materials, the mixture is prepared according to the chemical formula 0.75BiFeO3-0.25BaTiO3. Anhydrous ethanol is used as a solvent for grinding. The mixture is then dried and calcined at 750℃~850℃ for 2~4h to obtain 0.75BiFeO3-0.25BaTiO3 powder.

[0015] 3) Add MnO2 to the 0.75BiFeO3-0.25BaTiO3 powder from step 2) according to the chemical formula of 0.75BiFeO3-0.25BaTiO3-ywt%MnO2, grind with anhydrous ethanol as solvent, take out and dry to obtain the B layer material.

[0016] 4) After ball milling the A layer material and the B layer material respectively, add an appropriate amount of PVA to obtain the A layer raw material and the B layer raw material. Stack the A layer raw material and the B layer raw material in the order of A, B, A to form a sheet to obtain a plain sheet.

[0017] 5) Heat the raw sheet to 600℃ and hold for 1-3 hours to remove the adhesive, then heat to 950-1000℃ and hold for 4-6 hours. Cool to room temperature, brush silver on both sides, fire, and polarize in silicone oil to obtain piezoelectric ceramic.

[0018] In step 4), the amount of PVA in layer A is 10-15% of the weight of layer A; the amount of PVA in layer B is 10-15% of the weight of layer B.

[0019] In step 5), the silver-coated sheet is slowly heated to 600°C at a heating rate of 5°C / min and kept at that temperature for 2 hours.

[0020] In step 5), the polarization electric field is 4000-5000 V / mm, the temperature is 80-100℃, and the time is 15-20 min.

[0021] The present invention has the following beneficial effects:

[0022] 1) This invention uses an ABA stacked structure (BST-BFBT-BST) to form a heterostructure on the surface of BiFeO3-BaTiO3 ceramics through ion diffusion technology, thereby improving the disorder of Bi(Ba) and Fe sites and the relaxation ferroelectric properties of the system, and enhancing the depolarization temperature of the system.

[0023] 2) Ion diffusion technology was used to refine the ferroelectric domains on the surface of BiFeO3-BaTiO3 ceramics, reduce the domain inversion barrier, and improve the piezoelectric properties of the system.

[0024] 3) The ceramic prepared by this invention has excellent high-temperature piezoelectric properties and achieves a large piezoelectric coefficient d. 33 >120 pC / N and depolarization temperature T d It has a temperature greater than 400℃ and does not contain toxic elements such as Pb or precious metals such as Sc. Attached Figure Description

[0025] Figure 1 This is a dielectric temperature spectrum curve of the piezoelectric ceramic of Embodiment 1 of the present invention;

[0026] Figure 2 This is an in-situ dynamic depolarization curve of the piezoelectric ceramic of Embodiment 1 of the present invention. Detailed Implementation

[0027] The present invention will be further described below with reference to the embodiments, but the present invention is not limited to these embodiments.

[0028] Example 1

[0029] The general structural formula of the A-layer material is: BaTi 0.93 Sn 0.07 O3;

[0030] The general structural formula of the B-layer material is: 0.75BiFeO3-0.25BaTiO3-0.1wt%MnO2;

[0031] Preparation method:

[0032] 1) Preparation of layer A material:

[0033] Using analytically pure SnO2, BaCO3, and TiO2 as raw materials, according to BaTi 0.93 Sn 0.07 O3 was used as the raw material, zirconium balls were used as the grinding medium, and anhydrous ethanol was used as the solvent. The mixture was ball-milled for 12 hours, then dried at 80°C for 4 hours, and then pre-calcined at 1150°C for 3 hours to obtain the A layer material.

[0034] 2) Preparation of B-layer material:

[0035] Using analytical grade Bi₂O₃, Fe₂O₃, BaCO₃, and TiO₂ as raw materials, the mixture was prepared according to the chemical formula 0.75BiFeO₃-0.25BaTiO₃. Zirconium balls were used as the grinding medium, and anhydrous ethanol was used as the solvent. The mixture was ball-milled for 12 hours, then dried at 80°C for 4 hours, and finally pre-calcined at 750°C for 2 hours to obtain...

[0036] 0.75BiFeO3-0.25BaTiO3 powder;

[0037] Analytical grade MnO2 was added to 0.75BiFeO3-0.25BaTiO3 powder, with the weight of MnO2 added being 0.1% of the total weight of the mixed powder. Zirconium balls were used as the grinding medium, and anhydrous ethanol was used as the solvent. The mixture was ball-milled for 12 hours. After removal, it was dried at 80°C for 4 hours to obtain the B layer material.

[0038] 3) Pour the A layer material into a mortar and grind it, then add 10% PVA by weight of the A layer material to obtain the A layer raw material.

[0039] 4) Pour the B layer material into a mortar and grind it, then add 10% PVA by weight of the B layer material to obtain the B layer raw material.

[0040] 5) Layer A and layer B are stacked and pressed into sheets in the order A, B, A. The weights of the three layers are 0.1g, 0.25g, and 0.1g respectively, to obtain a plain sheet with a diameter of 10mm.

[0041] 6) Glue removal: Slowly heat the raw sheet to 600℃ at a heating rate of 5℃ / min, hold it at this temperature for 1 hour to remove the glue, then heat it to 950℃ and hold it for 4 hours. Cool it to room temperature in the furnace and process it into a thin sheet with smooth sides and a thickness of 0.5mm.

[0042] 7) Silver plating: To facilitate subsequent electrical performance testing, the sheet is silver-plated, i.e., silver is brushed onto both sides of the sheet using screen printing, with the conductive silver surface having a diameter of 8mm. Then, it is placed in a muffle furnace and held at 700℃ for 0.5h to obtain a silver-plated sheet.

[0043] 8) Polarization: The silver-plated sheet is polarized in silicone oil with a polarization electric field of 4000V / mm, a temperature of 80℃, and a time of 15min. The electric field is maintained and the sheet is cooled to room temperature.

[0044] The performance test results are as follows:

[0045] 169 81.652 295.61 405 3.54 563 404

[0046] Compare with Example 1

[0047] The general structural formula of the B-layer material is: 0.75BiFeO3-0.25BaTiO3-0.1wt%MnO2;

[0048] 1) Preparation of layer B material: Same as step 2) in Example 1;

[0049] 2) Pour the B layer material into a mortar and grind it, and add 10% of the weight of PVA to obtain the B layer raw material. Take 0.45g of the B layer raw material and press it into a sheet to obtain a plain sheet with a diameter of 10mm.

[0050] 3) Perform adhesive removal, silver plating, and polarization treatment on the raw sheet to obtain piezoelectric ceramics. This step is the same as steps 6), 7), and 8) in Example 1.

[0051] The performance test results are as follows:

[0052] 104 76.352 265.61 385 2.74 575 300

[0053] Example 2

[0054] The general structural formula of the A-layer material is: BaTi 0.91 Sn 0.09 O3;

[0055] The general structural formula of the B-layer material is: 0.75BiFeO3-0.25BaTiO3-0.3wt%MnO2;

[0056] Preparation method:

[0057] 1) Preparation of layer A material:

[0058] Using analytically pure SnO2, BaCO3, and TiO2 as raw materials, according to BaTi 0.91 Sn 0.09 O3 was used as the raw material, zirconium balls were used as the grinding medium, and anhydrous ethanol was used as the solvent. The mixture was ball-milled for 15 hours, then dried at 80°C for 4 hours, and then pre-calcined at 1200°C for 6 hours to obtain the A layer material.

[0059] 2) Preparation of B-layer material:

[0060] Using analytical grade Bi₂O₃, Fe₂O₃, BaCO₃, and TiO₂ as raw materials, the mixture was prepared according to the chemical formula 0.75BiFeO₃-0.25BaTiO₃. Zirconium balls were used as the grinding media, and anhydrous ethanol was used as the solvent. The mixture was ball-milled for 15 hours, then dried at 80°C for 4 hours, and finally pre-calcined at 850°C for 4 hours to obtain the desired product.

[0061] 0.75BiFeO3-0.25BaTiO3 powder;

[0062] Analytical grade MnO2 was added to 0.75BiFeO3-0.25BaTiO3 powder, with the amount of MnO2 added being 0.3% of the total weight of the mixed powder. Zirconium balls were used as the grinding medium, and anhydrous ethanol was used as the solvent. The mixture was ball-milled for 15 hours. After removal, it was dried at 80°C for 4 hours to obtain the B layer material.

[0063] 3) Pour the A layer material into a mortar and grind it, then add 15% PVA by weight of the A layer material to obtain the A layer raw material.

[0064] 4) Pour the B layer material into a mortar and grind it, then add 15% PVA by weight of the B layer material to obtain the B layer raw material.

[0065] 5) Layer A and layer B are stacked and pressed into sheets in the order A, B, A. The weights of the three layers are 0.1g, 0.25g, and 0.1g respectively, to obtain a plain sheet with a diameter of 10mm.

[0066] 6) Glue removal: Slowly heat the raw sheet to 600℃ at a heating rate of 5℃ / min, hold it at this temperature for 3 hours to remove the glue, then heat it to 1000℃ and hold it for 6 hours. Cool it to room temperature in the furnace and process it into a thin sheet with smooth sides and a thickness of 0.5mm.

[0067] 7) Silver plating: To facilitate subsequent electrical performance testing, the sheet is silver-plated, i.e., silver is brushed onto both sides of the sheet using screen printing, with the conductive silver surface having a diameter of 8mm. Then, it is placed in a muffle furnace and held at 700℃ for 0.5h to obtain a silver-plated sheet.

[0068] 8) Polarization: The silver-plated sheet is polarized in silicone oil with a polarization electric field of 5000V / mm, a temperature of 100℃, and a time of 20min. The electric field is maintained and the sheet is cooled to room temperature.

[0069] The performance test results are as follows:

[0070] 130 75.694 202.81 410 3.75 558 390

[0071] Compare with Example 2

[0072] The general structural formula of the B-layer material is: 0.75BiFeO3-0.25BaTiO3-0.3wt%MnO2;

[0073] 1) Preparation of layer B material: Same as step 2) in Example 2;

[0074] 2) Pour the B layer material into a mortar and grind it, and add 15% PVA by weight of the B layer material to obtain the B layer raw material. Take 0.45g of the B layer raw material and press it into a sheet to obtain a plain sheet with a diameter of 10mm.

[0075] 3) Perform adhesive removal, silver plating, and polarization treatment on the raw sheet to obtain piezoelectric ceramics. This step is the same as steps 6), 7), and 8) in Example 2.

[0076] The performance test results are as follows:

[0077] 102 71.694 200.67 388 2.98 560 381

[0078] Example 3

[0079] The general structural formula of the A-layer material is: BaTi 0.89 Sn 0.11 O3;

[0080] The general structural formula of the B-layer material is: 0.75BiFeO3-0.25BaTiO3-0.5wt%MnO2;

[0081] Preparation method:

[0082] 1) Preparation of layer A material:

[0083] Using analytically pure SnO2, BaCO3, and TiO2 as raw materials, according to BaTi 0.89 Sn 0.11 O3 was used as the raw material, zirconium balls were used as the grinding medium, and anhydrous ethanol was used as the solvent. The mixture was ball-milled for 14 hours, then dried at 80°C for 4 hours, and then pre-calcined at 1180°C for 4 hours to obtain the A layer material.

[0084] 2) Preparation of B-layer material:

[0085] Using analytical grade Bi₂O₃, Fe₂O₃, BaCO₃, and TiO₂ as raw materials, the mixture was prepared according to the chemical formula 0.75BiFeO₃-0.25BaTiO₃. Zirconium balls were used as the grinding media, and anhydrous ethanol was used as the solvent. The mixture was ball-milled for 14 hours, then dried at 80°C for 4 hours, and finally pre-calcined at 800°C for 3 hours to obtain...

[0086] 0.75BiFeO3-0.25BaTiO3 powder;

[0087] Analytical grade MnO2 was added to 0.75BiFeO3-0.25BaTiO3 powder, with the weight of MnO2 added being 0.5% of the total weight of the mixed powder. Zirconium balls were used as the grinding medium, and anhydrous ethanol was used as the solvent. The mixture was ball-milled for 14 hours. After removal, it was dried at 80°C for 4 hours to obtain the B layer material.

[0088] 3) Pour the A layer material into a mortar and grind it, then add 12% PVA by weight of the A layer material to obtain the A layer raw material.

[0089] 4) Pour the B layer material into a mortar and grind it, then add 12% PVA by weight of the B layer material to obtain the B layer raw material.

[0090] 5) Layer A and layer B are stacked and pressed into sheets in the order A, B, A. The weights of the three layers are 0.1g, 0.25g, and 0.1g respectively, to obtain a plain sheet with a diameter of 10mm.

[0091] 6) Glue removal: Slowly heat the raw sheet to 600℃ at a heating rate of 5℃ / min, hold it at this temperature for 2 hours to remove the glue, then heat it to 980℃ and hold it for 5 hours. Cool it to room temperature in the furnace and process it into a thin sheet with smooth sides and a thickness of 0.5mm.

[0092] 7) Silver plating: To facilitate subsequent electrical performance testing, the sheet is silver-plated, i.e., silver is brushed onto both sides of the sheet using screen printing, with the conductive silver surface having a diameter of 8mm. Then, it is placed in a muffle furnace and held at 700℃ for 0.5h to obtain a silver-plated sheet.

[0093] 8) Polarization: The silver-plated sheet is polarized in silicone oil with a polarization electric field of 4500V / mm, a temperature of 90℃, and a time of 18min. The electric field is maintained and the sheet is cooled to room temperature.

[0094] The performance test results are as follows:

[0095] 135 61.664 242.17 484 4.32 565 387

[0096] Compare with Example 3

[0097] The general structural formula of the B-layer material is: 0.75BiFeO3-0.25BaTiO3-0.5wt%MnO2;

[0098] 1) Preparation of layer B material: Same as step 2) in Example 3;

[0099] 2) Pour the B layer material into a mortar and grind it, and add 12% PVA by weight of the B layer material to obtain the B layer raw material. Take 0.45g of the B layer raw material and press it into a sheet to obtain a plain sheet with a diameter of 10mm.

[0100] 3) Perform adhesive removal, silver plating, and polarization treatment on the raw sheet to obtain piezoelectric ceramics. This step is the same as steps 6), 7), and 8) in Example 3.

[0101] The performance test results are as follows:

[0102] 106 58.023 243.84 450 3.89 567 374

[0103] Example 4

[0104] The general structural formula of the A-layer material is: BaTi 0.84 Sn 0.16 O3;

[0105] The general structural formula of the B-layer material is: 0.75BiFeO3-0.25BaTiO3-0.7wt%MnO2;

[0106] Preparation method:

[0107] 1) Preparation of layer A material:

[0108] Using analytically pure SnO2, BaCO3, and TiO2 as raw materials, according to BaTi 0.84 Sn 0.16 O3 was used as the raw material, zirconium balls were used as the grinding medium, and anhydrous ethanol was used as the solvent. The mixture was ball-milled for 12 hours, then dried at 80°C for 4 hours, and then pre-calcined at 1200°C for 3 hours to obtain the A layer material.

[0109] 2) Preparation of B-layer material:

[0110] Using analytical grade Bi₂O₃, Fe₂O₃, BaCO₃, and TiO₂ as raw materials, the mixture was prepared according to the chemical formula 0.75BiFeO₃-0.25BaTiO₃. Zirconium balls were used as the grinding media, and anhydrous ethanol was used as the solvent. The mixture was ball-milled for 15 hours, then dried at 80°C for 4 hours, and finally pre-calcined at 750°C for 4 hours to obtain...

[0111] 0.75BiFeO3-0.25BaTiO3 powder;

[0112] Analytical grade MnO2 was added to 0.75BiFeO3-0.25BaTiO3 powder, with the weight of MnO2 being 0.7% of the total weight of the mixed powder. Zirconium balls were used as the grinding medium, and anhydrous ethanol was used as the solvent. The mixture was ball-milled for 12 hours. After removal, it was dried at 80°C for 4 hours to obtain the B layer material.

[0113] 3) Pour the A layer material into a mortar and grind it, then add 12.5% ​​PVA by weight of the A layer material to obtain the A layer raw material.

[0114] 4) Pour the B layer material into a mortar and grind it, then add 12.5% ​​PVA by weight of the B layer material to obtain the B layer raw material.

[0115] 5) Layer A and layer B are stacked and pressed into sheets in the order A, B, A. The weights of the three layers are 0.1g, 0.25g, and 0.1g respectively, to obtain a plain sheet with a diameter of 10mm.

[0116] 6) Glue removal: Slowly heat the raw sheet to 600℃ at a heating rate of 5℃ / min, hold it at this temperature for 2 hours to remove the glue, then heat it to 1000℃ and hold it for 4 hours. Cool it to room temperature in the furnace and process it into a thin sheet with smooth sides and a thickness of 0.5mm.

[0117] 7) Silver plating: To facilitate subsequent electrical performance testing, the sheet is silver-plated, i.e., silver is brushed onto both sides of the sheet using screen printing, with the conductive silver surface having a diameter of 8mm. Then, it is placed in a muffle furnace and held at 700℃ for 0.5h to obtain a silver-plated sheet.

[0118] 8) Polarization: The silver-plated sheet is polarized in silicone oil with a polarization electric field of 4000V / mm, a temperature of 100℃, and a time of 15min. The electric field is maintained and the sheet is cooled to room temperature.

[0119] The performance test results are as follows:

[0120] 137 51.743 306.49 435 4.69 573 350

[0121] Compare with Example 4

[0122] The general structural formula of the B-layer material is: 0.75BiFeO3-0.25BaTiO3-0.7wt%MnO2;

[0123] 1) Preparation of layer B material: Same as step 2) in Example 3;

[0124] 2) Pour the B layer material into a mortar and grind it, and add 12.5% ​​PVA by weight of the B layer material to obtain the B layer raw material. Take 0.45g of the B layer raw material and press it into a sheet to obtain a plain sheet with a diameter of 10mm.

[0125] 3) Perform adhesive removal, silver plating, and polarization treatment on the raw sheet to obtain piezoelectric ceramics. This step is the same as steps 6), 7), and 8) in Example 3.

[0126] The performance test results are as follows:

[0127] 98 50.875 301.66 422 3.29 560 300

Claims

1. A bismuth ferrite-barium titanate piezoelectric ceramic with a heterostructure, characterized in that: This ceramic is made by sequentially stacking and pressing together layer A, layer B, and layer A: 1) After ball milling the A layer material and the B layer material respectively, an appropriate amount of PVA is added to obtain the A layer raw material and the B layer raw material. The A layer raw material and the B layer raw material are stacked and pressed into a sheet in the order of A, B, A to obtain a plain sheet. 2) Heat the raw sheet to 600℃ and hold it at that temperature for 1-3 hours to remove the adhesive, then heat it to 950-1000℃ and hold it at that temperature for 4-6 hours. Cool it to room temperature, brush silver on both sides, fire it, and then polarize it in silicone oil to obtain piezoelectric ceramic. The structural formula of the A-layer material is: BaTi (1-x) Sn x O3; The general structural formula of the B-layer material is: 0.75BiFeO3-0.25BaTiO3-ywt%MnO2; Where x represents the mole fraction, 0 < x ≤ 0.16; y = weight of MnO2 / total weight of B layer material × 100, and 0 < y ≤ 1.

2. The bismuth ferrite-barium titanate piezoelectric ceramic with a heterogeneous structure according to claim 1, characterized in that: The weight ratio of layer A material, layer B material, and layer A material is 1:2.5:

1.

3. The bismuth ferrite-barium titanate piezoelectric ceramic with a heterogeneous structure according to claim 1, characterized in that: 0.07≤x≤0.16, 0.1≤y≤0.

7.

4. The bismuth ferrite-barium titanate piezoelectric ceramic with a heterogeneous structure according to claim 3, characterized in that: x=0.07, y=0.

1.

5. The method for preparing the bismuth ferrite-barium titanate piezoelectric ceramic with a heterostructure as described in any one of claims 1 to 4, characterized in that: Includes the following steps: 1) Using SnO2, BaCO3, and TiO2 as raw materials, according to BaTi (1-x) Sn x The O3 chemical formula is used to prepare the ingredients, and anhydrous ethanol is used as the solvent for grinding. After drying, the material is fired at 1150℃~1200℃ for 3~6 hours to obtain the A layer material. 2) Using Bi2O3, Fe2O3, BaCO3, and TiO2 as raw materials, the mixture is prepared according to the chemical formula 0.75BiFeO3-0.25BaTiO3. Anhydrous ethanol is used as a solvent for grinding. The mixture is then dried and calcined at 750℃~850℃ for 2~4h to obtain 0.75BiFeO3-0.25BaTiO3 powder. 3) Add MnO2 to the 0.75BiFeO3-0.25BaTiO3 powder from step 2) according to the chemical formula 0.75BiFeO3-0.25BaTiO3-ywt%MnO2, grind with anhydrous ethanol as solvent, take out and dry to obtain the B layer material; 4) After ball milling the A layer material and the B layer material respectively, add an appropriate amount of PVA to obtain the A layer raw material and the B layer raw material. Stack the A layer raw material and the B layer raw material in the order of A, B, A to form a sheet to obtain a plain sheet. 5) Heat the raw sheet to 600℃ and hold for 1-3 hours to remove the adhesive, then heat to 950-1000℃ and hold for 4-6 hours. Cool to room temperature, brush silver on both sides, fire, and polarize in silicone oil to obtain piezoelectric ceramic.

6. The method for preparing the bismuth ferrite-barium titanate piezoelectric ceramic with a heterostructure according to claim 5, characterized in that: In step 4), the amount of PVA in layer A is 10-15% of the weight of layer A; the amount of PVA in layer B is 10-15% of the weight of layer B.

7. The method for preparing the bismuth ferrite-barium titanate piezoelectric ceramic with a heterogeneous structure according to claim 5, characterized in that: In step 5), the silver-burnt sheet is slowly heated to 600°C at a heating rate of 5°C / min and held at that temperature for 2 hours.

8. The method for preparing the bismuth ferrite-barium titanate piezoelectric ceramic with a heterogeneous structure according to claim 5, characterized in that: In step 5), the polarization electric field is 4000-5000 V / mm, the temperature is 80-100℃, and the time is 15-20 min.

Citation Information

Patent Citations

  • Sodium bismuth titanate base and barium titanate base multilayer composite piezoelectric film and making method thereof

    CN104045340A

  • High-temperature piezoelectric ceramic heterojunction material and preparation method thereof

    CN116063072A